Understanding parent behavioural intention in childcare service: The effect of perceived trust and emotional satisfaction - Nik Syuhailah, Nik Hussin; Zuraimi, Abdul Aziz; Nurul Ashykin, Abd Aziz; Nur A'mirah, Mohd Yaziz; Nor Hafiza, Othman; Hasif Rafidee, Hasbollah; Md Zaki, Muhamad Hasan (Malaysian Consumer and Family Economics Association, 2023)
Early childhood education and care services for children under four have become an essential societal concern in recent decades. Childcare services that are both affordable and of high quality may help to reconcile work and family life, promoting labour market participation and gender equality. Notably, there have been instances where childcare centres have failed to meet the government's minimum service requirements. As a result, the objective of this study is to determine the impact of perceived trust and emotional satisfaction on parent behavioural intentions in childcare services. The research framework on perceived trust and emotional satisfaction in childcare services was established utilising the Stimulus Organism Response (SOR) theory and Expectancy Confirmation Theory (ECT). This study selected a purposive sampling technique through the distribution of questionnaires to childcare providers. The study managed to collect responses from 364 respondents which were analysed using the Partial Least Square (PLS) Structural Equation Modelling approach. The result showed that perceived trust and emotional satisfaction were supported with behavioural intention. Apart from that, the mediation role of emotional satisfaction significantly impacted perceived trust and intention. Finally, the study concluded with the implication of the study theoretically and practically.